Spitz nevus: a case report of a benign melanocytic neoplasm with a review of recent advances - Kumar-Gupta,Sunil (2026)
Abstract Spitz nevus is a rare benign melanocytic lesion that can clinically mimic benign and malignant dermatological conditions. We report a case of a 22-year-old female who presented with a long-standing, asymptomatic nodule on her left cheek. The lesion was excised due to cosmetic concerns, and histopathological analysis confirmed the diagnosis of Spitz nevus. Given its clinical resemblance to malignant conditions, a complete surgical excision was performed for definitive diagnosis and cosmetic management. Recent studies highlight advances in molecular diagnostics and immunohistochemistry, which help differentiate Spitz nevus from malignant melanocytic neoplasms. This case underscores the necessity of histopathological and molecular evaluation in distinguishing Spitz nevus from other pigmented lesions.